Peri-electrode edema after deep brain stimulation. (January 2019) - Saitoh, Takuro; Enatsu, Rei; Mikami, Takeshi; Suzuki, Yuto; Kanno, Aya; Kitagawa, Mayumi; Mikuni, Nobuhiro
Highlights: Non-infectious peri-electrode edema after DBS surgery is not an uncommon phenomenon. Peri-electrode edema includes two types: limited deep and extensive surface edema. The diagnosis of this condition is important to avoid unnecessary electrode removal. Abstract: Peri-electrode edema can occur after deep brain stimulation (DBS). The diagnosis and management of peri-electrode edema may be challenging. We herein report non-infectious peri-electrode edema after the placement of DBS electrodes in patients with Parkinson's disease (PD). Fifteen patients who underwent DBS surgery between 2010 and 2018 at Sapporo Medical University were included to identify post-operative peri-electrode edema. Pre- and post-operative CT and MRI were retrospectively analyzed. Six patients showed hyperintensity around the electrodes on FLAIR/T2 MRI without neurological deficits. Two patients showed limited FLAIR and DWI hyperintensities in deep white matter, and microvessels may have been occluded in these patients. In five patients, MRI revealed extensive FLAIR or T2 hyperintensity in surface white matter around the electrodes without vessel injury, whereas DWI showed no abnormal signals. The eosinophil count was increased in one of these five patients. Peri-electrode edema after DBS surgery is not an uncommon phenomenon, and includes two types: (1) limited edema in deep white matter and (2) extensive edema in surface white matter. Different mechanisms may be associated with these types of edemas.